Sex-specific effects of alcohol on neurobehavioral performance and endoplasmic reticulum stress: an analysis using neuron-specific MANF deficient mice - Wen, Wen; Li, Hui; Lauffer, Marisol; Hu, Di; Zhang, Zuohui; Lin, Hong; Wang, Yongchao; Leidinger, Mariah; Luo, Jia (Frontiers in Pharmacology, 2024)
Excessive alcohol exposure can cause neurobehavioral deficits and structural alterations in the brain. Emerging research evidence suggests that endoplasmic reticulum (ER) stress plays an important role in alcohol-induced neurotoxicity. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is an ER stress inducible protein and is responsible to maintain ER homeostasis. MANF is highly expressed in both the developing and mature brain. We have previously shown that MANF deficiency exacerbated alcohol induced neurodegeneration and ER stress in the developing brain. However, little is known regarding the role of MANF in alcohol induced neuronal damage in the adult brain. In this study, we used a neuron-specific MANF knockout (KO) mouse model to investigate the effect of MANF deficiency on acute binge alcohol exposure-induced neurobehavioral deficits and ER stress. Adult male and female MANF KO mice and littermate controls received daily alcohol gavage (5 g/ kg) for 10 days and then subjected to a battery of neurobehavioral tests including rotarods, balanced beam, DigiGait, open field, elevated plus maze, Barnes maze, and three-chamber sociability task. Female MANF KO animals were more susceptible to alcohol-induced body weight loss. Alcohol exposure did not affect motor function, however female but not male MANF KO mice exhibited an increased locomotor activity in open field test. Learning and memory was not significantly impaired, but it was altered by MANF deficiency in females while it was affected by alcohol treatment in males. Both alcohol-exposed male and female MANF KO mice displayed increased sociability. Alcohol induced the expression of ER chaperones GRP78 and GRP94 and altered the levels of several unfolded protein response (UPR) and neuroinflammation markers in MANF KO mice in a sex-specific manner. The expression of MANF interacting proteins neuroplastin, PDIA1, and PDIA6 was increased in MANF KO mice, and was further induced by alcohol. In conclusion, alcohol exposure and neuronal MANF deficiency interacted to alter neurobehavioral outcomes, ER homeostasis and neuroinflammation in a sex-specific manner.